Improving the patient journey through a risk assessment approach for ESBL-E - Barratt, Ruth; Munro, Julianne (International Journal of Infection Control, 2019)
The increase in multidrug resistant organisms (MDRO), including Extended-spectrum beta-lactamase producing Enterobacteriaceae (ESBL-E), presents a challenge for infection prevention and control (IPC) teams to find adequate isolation facilities. Not all ESBL-E positive patients may present a risk for ongoing transmission and require isolation. Reducing unnecessary isolation can help with patient flow and reduce adverse events associated with isolation precautions. The Canterbury District Health Board IPC team aimed to improve the bed management and patient journey for ESBL-E colonised/infected patients through the introduction of a risk-assessment approach for deciding the IPC and isolation requirements for these patients. Hospital policy and procedures were revised to include a process for categorising patients according to their individual risk factors for transmission of ESBL-E. Each category requires a specific set of IPC measures. To facilitate the new policy, a colour assessment tool in the form of a poster was developed as a quick reference for staff. The new policy and poster were introduced across all hospital sites over several months. Several single rooms a day were freed up which facilitated overall bed management and patient flow. Patients with a low risk of transmission of ESBL-E benefited from a potential better journey of care. Furthermore, IPC surveillance reports did not demonstrate any increase in nosocomial ESBL-E cases. Implementing a risk assessment for the placement and care of ESBL-E patients can have a positive outcome for patients, families, staff and bed managers, while mitigating the risk of transmission of antimicrobial resistance.